Efficacy and safety of apremilast in subjects with moderate to severe plaque psoriasis: results from a phase II, multicenter, randomized, double-blind, placebo-controlled, parallel-group, dose-comparison study - Papp, K.A.; Kaufmann, R.; Thaçi, D.; Hu, C.; Sutherland, D.; Rohane, P. (Journal of the European Academy of Dermatology and Venereology, 2013)
Background  Apremilast, a small molecule specific inhibitor of phosphodiesterase 4, works intracellularly to modulate pro‐inflammatory and anti‐inflammatory mediator production. Objective  Assess apremilast efficacy and safety in moderate to severe plaque psoriasis. Methods  Phase II, 12‐week, multicenter, double‐blind, placebo‐controlled, parallel‐group, dose‐comparison study of 259 subjects randomized 1 : 1 : 1 to placebo, apremilast 20 mg QD or apremilast 20 mg BID. Results  More subjects receiving apremilast 20 mg BID achieved ≥ 75% reduction in Psoriasis Area and Severity Index (PASI‐75) vs. placebo (24.4% vs. 10.3%; P = 0.023). A similar proportion of subjects receiving apremilast 20 mg QD and placebo achieved PASI‐75 at week 12 [9/87 (10.3%, each group)]. Mean per cent reduction in PASI from baseline was 17.4% for placebo, 30.3% for apremilast 20 mg QD (P = 0.021 vs. placebo) and 52.1% for apremilast 20 mg BID (P < 0.001). Apremilast 20 mg BID significantly decreased mean body surface area involvement vs. placebo (30.8% vs. 3.2%; P < 0.001). The most common adverse events were headache, nasopharyngitis, diarrhoea and nausea. Most events (> 90%) were mild to moderate and did not lead to study discontinuation. Serious adverse events occurred in four placebo subjects (panic attack, hospitalization for rehabilitation, hospitalization for alcoholism, worsening psoriasis), one receiving apremilast 20 mg QD (knee surgery) and in one receiving apremilast 20 mg BID (worsening psoriasis). The panic attack was considered treatment‐related; both cases of worsening psoriasis occurred after medication discontinuation. No deaths or opportunistic infections were reported. Conclusion  Apremilast 20 mg BID for 12 weeks was effective and well tolerated in subjects with moderate to severe plaque psoriasis.